2017
DOI: 10.1016/j.eurpsy.2017.01.2127
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in schizophrenia: Selective impairment and factors that influence it

Abstract: Currently it is well known that schizophrenia is associated with cognitive impairment. Still there are many unresolved questions, such as whether cognitive deficit is total, what are the relationships of cognitive impairment with clinical features, demographic characteristics and different biomarkers, which could shed light on its pathogenesis. The aim of our study was to characterize cognitive impairment in schizophrenia and to find factors that may contribute to it. Sixty patients with paranoid schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To date, two to five cognitive trajectories have been identified in patients with psychosis who differ in terms of demographic and clinical characteristics . Cognitive alteration is also common in unaffected siblings, but to a lesser extent, and subtyping is relevant to identify meaningful homogeneous trajectories . In our previous cross‐sectional study, we demonstrated three subtypes of cognitive alteration (i.e., normal, mixed, and impaired) in siblings .…”
Section: Introductionmentioning
confidence: 79%
“…To date, two to five cognitive trajectories have been identified in patients with psychosis who differ in terms of demographic and clinical characteristics . Cognitive alteration is also common in unaffected siblings, but to a lesser extent, and subtyping is relevant to identify meaningful homogeneous trajectories . In our previous cross‐sectional study, we demonstrated three subtypes of cognitive alteration (i.e., normal, mixed, and impaired) in siblings .…”
Section: Introductionmentioning
confidence: 79%
“…Cognitive impairment in schizophrenia can be selective or general though the most common deficits occur in executive function, processing speed, memory (e.g. episodic, verbal and working), attention, verbal fluency, problem-solving and social cognition 8 11 . Patients harbor a wide range of subjectively defined symptoms, which together yields instinctively heterogeneous groups of people who are collectively diagnosed with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%